EKSPERIMENTAL TARIK BAJA TULANGAN PADA BETON VARIASI DIAMETER DAN PANJANG PENYALURAN MENURUT PERATURAN SNI 2847:2019 - Valentana Ardian Tarigan (Universitas Quality, 2022)
Reinforced concrete construction is inseparable from the use of reinforcing steel as a material that resists the tension that occurs in concrete structures. Steel material is used to carry out its duties to cover the weakness of concrete in terms of tensile loads. Tests are carried out to determine the magnitude of the difference in tensile strength of the reinforcing material being tested. Experiments on steel with a minimum yield stress of 280 MPa which is also known as plain reinforcing steel and reinforcing steel with a yield stress of at least 420 MPa or also known as fin reinforcing steel. The variation used in this test lies in the diameter of plain reinforcing steel with diameters of 8, 10 and 12 mm. Fin reinforcement steel with diameters of 10, 13 and 16 mm. The test results show that the deeper the reinforcing steel, the greater the required tensile strength. Other results show that fin steel reinforcement has a higher tensile strength than plain reinforcing steel.